PROBLEMS IN THE IMPLEMENTATION OF COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL) IN JOMBANG REGENCY - Permanasari, Lolita; Ngaisah, Siti (YURIS: Journal of Court and Justice, 2025)
Land registration is a critical government activity aimed at recording and maintaining physical and juridical data for land parcels, ensuring legal certainty for land rights holders. In Jombang Regency, despite 76.7% of 592,744 land parcels being titled, 100% titling has not been achieved. The government introduced the Complete Systematic Land Registration (PTSL) program, facilitated by Ministerial Regulations, to accelerate this process and provide legal certainty. However, the implementation of PTSL in Jombang Regency faces significant challenges, making it an important area for study. This research aims to analyze the implementation of the PTSL program in Jombang Regency, focusing on the challenges faced and the obstacles affecting its effectiveness in achieving legal certainty and reducing land disputes. This research uses an empirical juridical approach with a sociological juridical focus, drawing on primary data from interviews with the Jombang Regency Land Office and secondary data from laws and regulations related to land registration and PTSL, including Law No. 5/1960 and various government and ministerial regulations. This research revealed several technical constraints impacting PTSL implementation in Jombang Regency. These include a lack of human resources, limited timeframes for completion, insufficient public awareness regarding administrative requirements, and challenges in socialization and counseling. Further obstacles involve difficulties in retrieving and collecting juridical data, issues with physical data measurement due to terrain, and problems with certificate submission. Additionally, legal issues, particularly those related to inheritance and lost proof of ownership (Letter C), significantly impede the process.